2021
DOI: 10.3390/ani11051263
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Habitat Elements from Bird Images Using Deep Convolutional Neural Networks

Abstract: With the rapid development of digital technology, bird images have become an important part of ornithology research data. However, due to the rapid growth of bird image data, it has become a major challenge to effectively process such a large amount of data. In recent years, deep convolutional neural networks (DCNNs) have shown great potential and effectiveness in a variety of tasks regarding the automatic processing of bird images. However, no research has been conducted on the recognition of habitat elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…There is a huge amount of decrease in the bird species, and it has a negative impact on both biodiversity and human lives. [18] Habitat Ensemble models are better than DenseNet201 and ResNet152v2 models.…”
Section: Preserve the Bird Speciesmentioning
confidence: 93%
See 1 more Smart Citation
“…There is a huge amount of decrease in the bird species, and it has a negative impact on both biodiversity and human lives. [18] Habitat Ensemble models are better than DenseNet201 and ResNet152v2 models.…”
Section: Preserve the Bird Speciesmentioning
confidence: 93%
“…A paper that uses a deep convolutional neural network [18] to identify birds' images was published. The author used habitat elements of bird images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We design the machine learning model based on a CNN [26]. CNN-based models are widely used in the field of image processing.…”
Section: Signal Processing and Machine Learningmentioning
confidence: 99%
“…Others, as Chilson et al (2019) and Wang et al (2021), identified birds' habitat elements using radar data and photographic images, respectively. Deneu et al (2021) used CNNs to improve species distribution modeling by capturing complex spatial structures of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al ( 2018 ) used CNNs (and Support Vector Machine) with satellite images to model the habitat suitability for a migratory geese species. Others, as Chilson et al ( 2019 ) and Wang et al ( 2021 ), identified birds' habitat elements using radar data and photographic images, respectively. Deneu et al ( 2021 ) used CNNs to improve species distribution modeling by capturing complex spatial structures of the environment.…”
Section: Introductionmentioning
confidence: 99%